First detection of porcine circovirus type 3 in Japan - HAYASHI, Shizuka; OHSHIMA, Yoshiyuki; FURUYA, Yoshiaki; NAGAO, Aki; OROKU, Kazuki; TSUTSUMI, Nobuyuki; SASAKAWA, Chihiro; SATO, Tetsuo (Journal of Veterinary Medical Science, 2018)
Porcine circovirus associated diseases (PCVAD) have multiple manifestations that have been attributed to porcine circovirus type 2 (PCV2). Recently, a novel porcine circovirus, PCV type 3 (PCV3), was identified in pigs with systemic inflammation of unknown etiology. In this study, we tried to detect the PCV3 genome in tissue samples collected from Japanese pig herds in 2016. The PCV3 genome was detected by PCR in 7 of 73 samples. The homology between each Japanese strain was 99.5% for the full-length sequence and 98.9 to 99.2% for the open reading frame 2. These results suggest that PCV3 has already invaded Japanese pig farms.